Maternal age - a risk factor for congenital hydrocephalus - T. T. Kitova; B. D. Kitov; E. H. Uchikova; N. T. Ahmad (Clinical and Experimental Obstetrics & Gynecology)
Aims: The aim of this study was to determine whether maternal age on its own and, in combination with other risk factors and associated anomalies, are risk factors for the development of hydrocephalus. Materials and Methods: One-hundred-eighty-two fetuses with congenital hydrocephalus (CH) were studied by fetal autopsy. Sixty-nine of them (38%) had Isolated Hydrocephalus (IH) and 113 (62%) -Associated Hydrocephalus (AH). Most fetuses (172) were received over a period of three years (2006-2009), out of 21,316 births at an Embryo-Fetopathologic Clinic, the Centre for Maternity and Neonatology, Tunis, Tunisia. The remaining ten fetuses were obtained from an Obstetrics and Gynecology Clinic at University Hospital, Plovdiv, Bulgaria in 2016, out of 2, 104 births. Results: When the mother’s age is over 40 years and consanguinity is present, the risks of CH and associated hydrocephalus is increased [OR = 18.750 CI (1.162-302.544)], [OR = 11.667 CI (0.924-147.298)]. The risk of CH is 35-fold greater with maternal age over 40 years and lissencephaly [OR = 35,000 CI (1.743-702.993)]. There is also moderate risk of CH with trisomies and maternal age over 38 years [OR = 12.740 CI (3.402-7.710)]. Conclusions: At a time when the number of women giving birth for the first time after the age of 35 years increases, maternal age should be considered a risk factor for the occurrence of CH. This possibility is increased when combined with other maternal or exogenous risk factors, and in the presence of associated malformations, such as aqueductal stenosis, polygyria, lissencephaly, and trisomies. Conclusion: A maternal age over 35 years should be considered a risk factor for the occurrence of hydrocephalus.